PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP PEMAHAMAN BELAJAR IPAS SISWA SD - Fatma Ramanda; Firman; Desyandri (EDU RESEARCH, 2023)
In the midst of advances in information technology, integrating innovative learning media is becoming increasingly important. One learning media that is attracting attention in this context is Wordwall, an online platform that provides a variety of interactive activities, including word puzzles, quizzes and other educational games. The aim of this research is to determine the effect of using wordwall media on the learning understanding of class IV students at SD 11 Lubuk Buaya, Padang. The research method used is quantitative research with an experimental approach. The population of this study were all students at SDN 11 Lubuk Buaya, Padang City. The sample for this research was 30 class A students and 30 class B students. The instruments used were in the form of comprehension tests and observation sheets. The analysis technique used is the t-test. The results of the research found that there was a significant influence from the use of Wordwall media on the understanding of science learning for class IV students at SDN 11 Lubuk Buaya, Padang City. Keyword: Wordwall media, understanding, IPAS